A Study-Of The Self-Loci Of Control Towards Students' Achievements In Distance Education. - A Ghani, Noraida; Atan, Hanafi; Fa Jelani, Maya; Majid, Omar; A Rahman, Zuraidah; Midrus, Rozhan (2004)

(untitled)
This article reports on the study undertaken to elucidate the role of the self-loci of control towards the achievements of distance education learners in their endeavour to pursue life-long learning. -Six dimensions of the self-loci of control were studied, namely time management, the learning style, attitude and perception, motivation, self directedness and past learning experiences.